Impact of toluene exposure on MDA, creatinine, and BUN levels in printing workers at Airlangga University Press, Surabaya - Tualeka, Abdul Rohim; Putro, Gurendro; Ruyani, Aceng; Susmiati, Susmiati; Santjaka, Aris; Rahmania, Aisy; Utami, Tri Niswati; Maryiantari, Ellyza Setya; Rokhmah, Dewi; Nisa S, Farhana Syahrotun; Muhammad, Dimas Rahadian Aji; Irawan, Roy Januardi; et al. (Sami Publishing Company, 2025)
The concentration of toluene in the industry has been above the threshold. This study aims to analyze the effect of toluene exposure on MDA, creatinine and BUN levels in Airlangga University Press Surabaya printing workers. This type of study is observational. The design of this study was cross sectional.The location of this research was carried out in the printing industry of Airlangga University Press Surabaya starting in October 2022 – January 2023.The sample size is a total population of 14 respondents. Research variables include respondent characteristics, toluene, bun, creatinine. Primary data collection on respondents' characteristics was conducted through interviews using questionnaires and observations. Data Analysis is used Descriptive analysis, Crosstabulation, Strong Analysis of the impact. The maximum value of the toluene concentration obtained is 3.4465 ppm and the minimum value is <0.0516 ppm. Theaverage level of Malondialdehyde (MDA) is 4.184 nmol/ml with the maximum value is 5.134 nmol/ml while the minimum value is 3.284 nmol/ml. The standard deviation for MDA levels is 0.517. Workers who had MDA levels ≥ 1.076, workers aged <37 years and ≥ 37 years had abnormal MDA levels. Workers had a maximum creatinine level value of 1.17 mg/dL and a minimum value of 0.65 mg/dL. Ror the average value of BUN levels is 35 ng / dL. The most influential toluene exposure on BUN levels was obtained Standard Coeficient (Beta) value of 0.788 then MDA levels with Standard Coeficient (Beta) value of 0.762 and finally creatinine levels showed a value of 0.586. Blood tests showed that the worker had high levels of MDA, and for creatinine levels and BUN levels in the normal category. Toluene exposure has the most effect on BUN levels, then MDA levels, and creatinine levels. © 2025 by SPC (Sami Publishing Company).